An online cognitive authentication and trust evaluation application programming interface for cognitive security gateway based on distributed massive Internet of Things network. (8th December 2020) - Chen, Hsing‐Chung; Yang, Wei‐Ju; Chou, Chao‐Lung
Abstract: As the number of Internet of massive Things (IoT) applications grows in vehicles, factory machinery, smart buildings, and city infrastructure, a secure and automated solution of enabling a mesh network for transactional processes is a significant demand. However, the trust evaluation among those unknown IoT devices which communicate to each other are still the high demand in distributed massive IoT network. In this paper, an online cognitive authentication and trust evaluation decision application programming interface (API) for Cognitive Security Gateway (CSG) based on distributed massive IoT network is proposed. The online cognitive security APIs consisting of cognitive authentication sub‐API, cognitive trust evaluation sub‐API and cognitive authorization sub‐API are designed for distributed massive IoT applications. The modified electronic product code (EPC) Class1Gen2 tags generated by CSG server is and proposed to be the online identity for the system used. Moreover, both the security analyses and trust evaluations for the CSG are discussed. Finally, the proposed system is shown that it is an appropriate solution for solving the online authentication problem in distributed cognitive IoT network.